Role of Proton Pump Inhibitors in Chronic Cough (Medical Forum Monthly, 2024)
Objective: To see the effectiveness of Proton Pump Inhibitors in patients with chronic cough at Liaquat University Hospital.Study Design: Observational studyPlace and Duration of Study: This study was conducted at ENT Department, Liaquat University Hospital, Jamshoro/Hyderabad from November 2010 to October 2011.Materials and Methods: Irrespective of age and gender 109 cases were recorded with history of chronic cough. After getting a detailed History all the cases were examined thoroughly for any pathology in Nose, Nasopharynx, Sinuses, Throat and Larynx in ENT department and then Sent to Physician to find or exclude the pathology in chest and Gastro intestinal tract. Required investigations were carried out in selected cases. All the cases after diagnosis were selected for PPI treatment for 30 days. Patient’s response to the treatment was recorded. All the data regarding sign symptoms, clinical diagnosis, duration of cough and response of the cases to PPI treatment was entered on Performa for analysis.Results: 109 cases were chosen in present study with chronic cough, majority of the cases 55/(50.45%) were found with age group of 41-60 years. Female were found in the big percentage 63/(57.79%), as compare to male 46/(42.20%), mostly 86/(78.89%) cases had duration of cough under VIII weeks.39/(35.77%) cases were noted with feeling of lump in throat and this was commonest symptom. 57/(52.29%) patients were found with complete response, 35/(32.11%) patients were noted with partial response and continued for some more days, while 17/(15.59%) patients had not respond to PPI treatment and those were advised some other investigations and treatment.